Adherence to guideline recommendations for multimodality treatment of patients with pT2–3 M0 non‐urothelial carcinoma of the urinary bladder: Temporal trends and survival outcomes. (14th March 2020) - Mistretta, Francesco A; Negrean‐Dzyuba, Cristina; Palumbo, Carlotta; Pecoraro, Angela; Knipper, Sophie; Tian, Zhe; Musi, Gennaro; Montanari, Emanuele; Perrotte, Paul; Briganti, Alberto; Shariat, Shahrokh F; Saad, Fred; et al.
Abstract : Objectives: To analyze contemporary multimodality treatment rates, defined as radical cystectomy plus chemotherapy and/or radiotherapy, for pT2–3 any N‐stage M0 non‐urothelial carcinoma of urinary bladder patients. Additionally, we tested for the effect of multimodality treatment versus radical cystectomy alone on cancer‐specific mortality. Methods: Within the Surveillance, Epidemiology and End Results database (2004–2015), 887 pT2–3 any N‐stage M0 non‐urothelial carcinoma of urinary bladder patients treated with radical cystectomy were identified. Kaplan–Meier plots, and univariable and multivariable Cox regression analyses focused on cancer‐specific mortality rates. Results: Squamous cell carcinoma was recorded in 499 (56.3%) patients, neuroendocrine carcinoma in 246 (27.7%) and adenocarcinoma in 142 (16.0%). The highest proportion of multimodality treatment patients was recorded in neuroendocrine carcinoma (69.1%), relative to adenocarcinoma (34.5%) and squamous cell carcinoma (26.4%). A statistically significant annual increase was recorded in multimodality treatment rates in neuroendocrine carcinoma patients (46.7–74.2%, P  < 0.01), but not in adenocarcinoma or squamous cell carcinoma patients. The 5‐year cancer‐specific mortality rate in neuroendocrine carcinoma patients was significantly lower after multimodality treatment versus radical cystectomy alone (37.0% vs 51.5%; P  < 0.01), but no statistically significant differences were recorded in both adenocarcinoma (46.1% vs 35.5%; P  = 0.8) and squamous cell carcinoma (41.4% vs 31.1%; P  = 0.8) patients. In multivariable analyses, for neuroendocrine carcinoma patients, multimodality treatment was an independent predictor of a lower cancer‐specific mortality rate (hazard ratio 0.58, P  = 0.03). Conclusions: Multimodality treatment has been increasingly used during the study period in neuroendocrine carcinoma patients, and it has translated into a cancer‐specific mortality benefit. This is not the case for other non‐urothelial carcinoma of urinary bladder patients, such as adenocarcinoma or squamous cell carcinoma.